Coconut Shell Applications For Making Antenna Tv In Madrasah Aliyah Muhammadiyah 09 Kwala Madu - Supeno, Minto; Ginting, Mimpin (Talenta Publisher, 2019)
Shell antenna is an original UHF antenna technology, produced from research continuous and observations for years. Natural polymeric material from a combination soft-hard that can be relied upon as a television antenna at a radius of 180 km, with antenna gain 11 dB, which can be used in the lowlands, highlands and at the bottom of the sea. This antenna is very good performance for high frequencies. The UHF shell antenna prototype consists of: (l) Two rectifiers the first wave from the shell pores and the second from the smooth almonium plate that is mounted lined up inside the shell parts; (2) reflector of almonium; and (3) carbonyl groups and micro elements as a receiver. The advantages of this antenna can close up more clear, clear, cool clearer eyes and reception, can be used in the lowlands, highlands and at the bottom sea, this antenna is very good performance for high frequencies, can close up clearer, clear, cool in the eyes and voice reception clearer.